2018
DOI: 10.3389/fgene.2018.00345
|View full text |Cite
|
Sign up to set email alerts
|

The Telomerase Complex Directly Controls Hematopoietic Stem Cell Differentiation and Senescence in an Induced Pluripotent Stem Cell Model of Telomeropathy

Abstract: Telomeropathies are rare disorders associated with impaired telomere length control mechanisms that frequently result from genetic mutations in the telomerase complex. Dyskeratosis congenita is a congenital progressive telomeropathy in which mutation in the telomerase RNA component (TERC) impairs telomere maintenance leading to accelerated cellular senescence and clinical outcomes resembling premature aging. The most severe clinical feature is perturbed hematopoiesis and bone-marrow failure, but the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…DC patients carrying TERC mutations develop aplastic anemia and cancer more frequently than other DC patients (7), suggesting noncanonical roles for TERC in DC pathogenesis. Recent studies have shown that TERT-TERC complexes bind to ribosomal DNA promoters and stimulate transcription by Pol I during regeneration and in tumorigenesis (29) and that inhibition of TERT and TERC impaired myelopoiesis of human iPS cells independently of telomere length (30). We have found that terc plays an essential role in myelopoiesis in zebrafish by regulating myeloid gene expression but in a manner independent of telomere length and also TERT (19).…”
Section: Discussionmentioning
confidence: 65%
“…DC patients carrying TERC mutations develop aplastic anemia and cancer more frequently than other DC patients (7), suggesting noncanonical roles for TERC in DC pathogenesis. Recent studies have shown that TERT-TERC complexes bind to ribosomal DNA promoters and stimulate transcription by Pol I during regeneration and in tumorigenesis (29) and that inhibition of TERT and TERC impaired myelopoiesis of human iPS cells independently of telomere length (30). We have found that terc plays an essential role in myelopoiesis in zebrafish by regulating myeloid gene expression but in a manner independent of telomere length and also TERT (19).…”
Section: Discussionmentioning
confidence: 65%
“…In fact, TERC 2/2 mice have shortened lifespans, signs of pulmonary aging, and induced senescence when compared with TERC 1/1 mice (61,62). Furthermore, knockdown of hTR in human induced pluripotent stem cells results in cellular senescence (63). SIRT1 also regulates cellular senescence, as SIRT1 inhibition has been shown to induce cellular senescence, similar to the effect of hTR ablation (64)(65)(66).…”
Section: Discussionmentioning
confidence: 95%
“…Using the same Matrigel™ coating for these dishes that we also use for the normal plastic dishes, we see a slightly better cell attachment (approximately 10–15% more cells attach to the Nunclon™ Delta surface-treated dishes). These Nunclon™ Delta surface-treated dishes are also used by other laboratories for cultivating iPSC [ 36 , 94 ]. The slightly better attachment may be caused by the hydrophilic surface and/or by the high surface roughness.…”
Section: Thawing Of Ipscmentioning
confidence: 99%